Niveles de sal y vinagre para la conservación de huevos cocidos de codorniz (Coturnix coturnix japónica) - Marín Álvarez, Louison Steven (2015)
The study was carried out in "The Mary" Experimental Farm of the UTEQ, indicating as objective to determine the effect of the brine in the physical characteristics-chemical, microbiological and sensory in the conservation of quail eggs and establish the costs of production and profitability levels. We used a completely randomized design (CRD) in accordance with trifactorial two levels of vinegar (8 and 12 %) by three concentrations of salt (2, 3, 4 %) and two times of conservation (30 and 45 days) with three replications. The data obtained in the respective analyzes conducted for the study of the proposed variables were entered into the program INFOSTAT, which allowed us to perform a statistical analysis and see the variations between the different treatments studied. It was followed by a organoleptic analysis achieving establish sensory profiles of the quails eggs and their acceptability by the group of panelists, which went to the T3 treatment that corresponds to 8 per cent of vinegar, 3 % salt and 30 days of conservation. Unlike the best level of vinegar with 12 %, and the best level of salt to 3 per cent and the best time for the conservation of 30 days according to the factors, in relation to the interactions was obtained that the treatment T8 register the best features in acidity, energy, fat, and microbiological best individuals. The costs of the best treatment (T9) is $3.262 with a profitability of 0,839 %.